Listening Niches across a Century of Popular Music - Krumhansl, Carol Lynne (Frontiers in Psychology, 2017)
This article reports the results of a study spanning a century of popular music, divided into 10 decades, with participants varying in age from their mid-teens to their mid-70s. It traces the music media with which they listened in different periods of their lives. It asks about whether they know and like the music in each decade, and their emotional reactions. Finally, it asks whether the music is associated with autobiographical memories and, if so, with whom they were listening or whether they were listening alone. The results show a regular progression through the life span of listening with different individuals (from parents to children) and with different media (from records to digital downloads). A number of effects found in previous studies were replicated, but the study also showed interactions with the birth cohorts. Overall, there was a song specific age effect with preferences for music of late adolescence and early adulthood; however, this effect was stronger for the older participants. In addition, there were preferences for music of the 1940s, 1960s, and 1980s that were stronger for the younger participants. Music of these decades also produced the strongest emotional responses and coincided with the introduction of important new music technologies, particularly long playing records, tape cassettes, and CDs. When growing up, the participants tended to listen to the older music on the older media, but rapidly shifted to the new music technologies in their last teens and early twenties. Younger listeners are currently listening less to music, suggesting an important role of socially sharing music. Finally, the oldest listeners had the broadest taste, liking music that they had been exposed to in different “listening niches” over their lifetimes.